TOWARDS A NEW CARIBBEAN CINEMA? AN INTERVIEW WITH JAMAICAN FILMMAKER STORM SAULTER (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Storm Saulter (www.stormsaulter.com) is a Jamaican filmmaker, photographer, and visual artist. He is best known for directing the award-winning Jamaican feature film Better Mus’ Come (2010) and for co-founding New Caribbean Cinema, a DIY (Do It Yourself) collective of young filmmakers in Jamaica and the wider Caribbean dedicated to creating a new wave of Caribbean filmmaking (www.newcaribbeancinema.com). Together they have already produced a series of short films under the title Ring di Alarm(2012), which was shown around the world before coming home to packed theatres in Kingston in August 2014. In the following interview, which took place via Skype on November 12, 2014, Storm Saulter talks about his career as a filmmaker in Jamaica and discusses his work in the context of Caribbean cinema and society.